IMPLEMENTASI EKATE.APP SEBAGAI MEDIA PEMBELAJARAN PADA MATERI EKONOMI KREATIF DI TINGKAT SEKOLAH MENENGAH ATAS - Dwiasa Sambhawa Dharma; Sauca, Dhinar Mawanti (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2025)
Information and communication technology in learning has a role as an intermediary in the implementation of knowledge transfer without completely eliminating the initial learning model that takes place in face-to-face classes. The use of technology as a creative and interesting learning medium, it is important for teachers to pay attention to the syllabus and learning outcomes of the content and materials to be used. The purpose of this study is to find out the results of the implementation of the